Gut-brain peptides in corticostriatal-limbic circuitry and alcohol use disorders - Vadnie, Chelsea A.; Park, Jun Hyun; Abdel Gawad, Noha; Ho, Ada Man Choi; Hinton, David J.; Choi, Doo-Sup (Frontiers in Neuroscience, 2014)
Peptides synthesized in endocrine cells in the gastrointestinal tract and neurons are traditionally considered regulators of metabolism, energy intake, and appetite. However, recent work has demonstrated that many of these peptides act on corticostriatal-limbic circuitry and, in turn, regulate addictive behaviors. Given that alcohol is a source of energy and an addictive substance, it is not surprising that increasing evidence supports a role for gut-brain peptides specifically in alcohol use disorders (AUD). In this review, we discuss the effects of several gut-brain peptides on alcohol-related behaviors and the potential mechanisms by which these gut-brain peptides may interfere with alcohol-induced changes in corticostriatal-limbic circuitry. This review provides a summary of current knowledge on gut-brain peptides focusing on five peptides: neurotensin, glucagon-like peptide 1, ghrelin, substance P, and neuropeptide Y. Our review will be helpful to develop novel therapeutic targets for AUD.